Bodies in the city: Athenian street art and the biopolitics of the 'Greek crisis' (Urban Art and the City Creating, Destroying, and Reclaiming the Sublime., 2020)
From the onset of the so-called “Greek crisis” (a sovereign-debt default in late 2009 and the subsequent, and ongoing, attempts on behalf of successive Greek governments at securing adequate bailout aid from the EU and the IMF), a new breed of biopolitics seems to have been in place. Classical antiquity has always played a crucial part in the forging of modern Greek social and cultural identities; in the framework of the “Greek crisis”, however, classical heritage and its visual output has been used both as an emancipatory tool against the country’s debtors as well as a disciplinary device on behalf of its critics. In this paper, a number of earlier and more recent Athenian graffiti will be discussed, directly or indirectly incorporating themes from Greek art in order to express their makers’ sentiments – as well as the frustrations of their public at large. Contrasting unauthorized examples of Athenian street art with some centrally-sponsored recent examples also employing classicizing imageries, the paper will explore the ways in which classical heritage finds itself entangled with the neoliberal biopolitics at work in Greece since 2009.